Slowly rotating black holes in Einstein-æther theory - Barausse, Enrico; Sotiriou, Thomas P.; Vega, Ian (American Physical Society, 2016)
We study slowly rotating, asymptotically flat black holes in Einstein-æther theory and show that solutions that are free from naked finite area singularities form a two-parameter family. These parameters can be thought of as the mass and angular momentum of the black hole, while there are no independent æ ther charges. We also show that the æ ther has nonvanishing vorticity throughout the spacetime, as a result of which there is no hypersurface that resembles the universal horizon found in static, spherically symmetric solutions. Moreover, for experimentally viable choices of the coupling constants, the frame-dragging potential of our solutions only shows percent-level deviations from the corresponding quantities in General Relativity and Hořava gravity. Finally, we uncover and discuss several subtleties in the correspondence between Einstein-æther theory and Hořava gravity solutions in the c ω →∞ limit.